The Role of Journal Writing in Senior High School Students’ Attitude toward Mathematics - Ivee Kalalo Guce (International Journal of Evaluation and Research in Education (IJERE), 2018)
The study investigated the influence of journal writing on the senior high school students’ attitude toward mathematics. A mixed-method approach, particularly the convergent parallel design, was used in this study. Using Scale on Attitude Toward Mathematics (SATM) (Guce & Talens, 2013), the students’ attitude toward the subject was measured in four subscales—liking or disliking mathematics, tendency to engage in or avoid mathematical activities, belief that one is good or bad in mathematics and belief that mathematics is useful or useless. Using focus group discussion, the insights of the students on journal writing as a mathematics class activity were gathered. Results using quantitative data revealed positive significant differences in the attitude of the respondents in terms of (i) liking mathematics and (ii) having the tendency to engage in mathematical activities. This aligned with the result in the focus group discussion which suggested that students perceive journal writing as a helpful tool for them to enjoy mathematics and engage in it. The activity, thus, may be regarded as a means to improve students’ attitude toward mathematics.